2001
DOI: 10.2989/00306520109485283
|View full text |Cite
|
Sign up to set email alerts
|

Distances moved and elapsed times between ringing and recovery for three Ploceus weavers in southern Africa

Abstract: Oatley, TB. & Underhill, L.G. 2001. Distances moved and elapsed times between ringing and recovery for three Ploceus weavers in southern Africo. Ostrich 72( 1&2): 41-44.A model-free method utilizing randomization tests was used to compare the distances moved and elapsed times between ringing and recovery. The method wos applied to ring recovery data for three weavers in southern Africa, the Cape, Ploceus capens;s, Masked, P. ve/atus, and Spotted-backed, P. cucullatus, Weavers. We found large differences in ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…2 also suggests that some of the survival estimates for the Ploceinae (true weavers) are lower than might be expected for birds of that body mass and clutch size. The low survival estimate for Quelea quelea might be related to its atypical nomadic lifestyle (Harrison et al 1997) while the low estimate for P. capensis might reflect its relatively southern and temperate distribution (Oatley and Underhill 2001). Excluding these two estimates decreases the residual adult survival for the Ploceinae from −9 (as in Fig.…”
Section: Is Survival Related To Clutch Size In Southern African Birds?mentioning
confidence: 96%
“…2 also suggests that some of the survival estimates for the Ploceinae (true weavers) are lower than might be expected for birds of that body mass and clutch size. The low survival estimate for Quelea quelea might be related to its atypical nomadic lifestyle (Harrison et al 1997) while the low estimate for P. capensis might reflect its relatively southern and temperate distribution (Oatley and Underhill 2001). Excluding these two estimates decreases the residual adult survival for the Ploceinae from −9 (as in Fig.…”
Section: Is Survival Related To Clutch Size In Southern African Birds?mentioning
confidence: 96%
“…Size is thus unlikely to be a major determinant of wing-moult duration. Oatley & Underhill (2001) concluded that Cape Weavers on average moved longer distances and were shorter-lived than either Masked or Spotted-backed Weavers, on the basis of which one might have predicted a shorter moult period for this species.…”
Section: Comparison Of Species In the Eastern Capementioning
confidence: 96%